Efeitos do exercício físico não-supervisionado na capacidade funcional e na qualidade de vida de portadores de insuficiência cardíaca crônica - MORAIS, Elizabeth Rodrigues de (2010)
Introduction: Patients with chronic heart failure often have limiting symptoms such as breathlessness, fatigue and effort intolerance that impair substantially the functional capacity and quality of life. It is known that physical exercise is an important adjuvant treatment of heart failure. When performed supervised, offers many benefits, among them improved functional capacity and quality of life. On the other hand, little is known about these effects when performed in a unsupervised manner. Objectives: To evaluate the impact of a program of unsupervised exercise on the quality of life and functional capacity of patients with chronic heart failure, and assess adherence to the proposed exercise. Methods: Using a controlled clinical trial randomized into two groups, 22 patients with heart failure, who attended the outpatient Heart Failure, Hospital das Clinicas, Federal University of Goias, aged between 18 and 85 years, both sexes, class II or III and of any origin. The GT-training group (n = 13) were walking on a unsupervised for 10 weeks and educational workshop. The control group-CG (n = 9) received only educational workshop. Both groups underwent assessment of functional test through the six-minute walk (6MWT) and the assessment of quality of life using the SF-36, pre and post intervention. Results: The average age of TG was 62.1 ± 11.7 years and the CG was 65.9 ± 11.5 years. Both have increased the distance walked during the six-minute walk, the GT grew 64.1 m (p = 0.004) and GC increased 29.1 m (p = 0.03). Regarding quality of life, the TG showed improvement in six areas of the SF-36: physical functioning (p = 0.003), physical (p = 0.01), pain (p = 0.03), Social (p = 0.02), emotional role (p = 0.02) and mental health (p = 0.003). The GC showed improvement only in the mental health domain (p = 0.03). The adherence of the GT was 97% Conclusion: The unsupervised exercise was effective in improving functional capacity and quality of life in patients with chronic heart failure. The exercise adherence proposed was satisfactory.